FORENSIC ASPECT OF SEXUAL DIMORPHISM FROM ANTHROPOMETRIC MEASUREMENTS ON ADULT HUMAN DRY HIP BONES (Journal of Forensic Medicine & Toxicology, 2023)
Background: Hip bone is a large irregular bone of forensic interest, as it doesn’t get easily disintegrated in accidents. This is important physical evidence to biological anthropologist’s in interpreting sex, stature etc. Material and methods: Diameter of acetabulum, distance between pubic tubercle and acetabular margin, length of pubis, length of ischium, ischiopubic index, Sciatic Notch (SN) index, Chilotic line index are some morphometric variables considered as tool for determination of sex on adult dry hip bone. Results: Chilotic index and SN index have been shown to be statistically significant (p value 0.000 and 0.001 respectively) in estimation of sex. Conclusion: Different morphometric variables are discussed, whereas, estimation of sex from chilotic index and SN index are recommended.
Keywords: Forensic science; forensic anthropology; anatomy; osteology; pelvic bones; sex characteristics